THE EFFECT OF WATER RESISTIVITY ON THE CORROSION RATE OF STEEL PLATE IRRIGATION IN LABORATORY - puji astuti ibrahim (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2022)
Corrosion is one of the processes of metal damage or degradation due to redox reactions between a metal and various substances in its environment that produce undesirable compounds. In the water one of the environmental parameters is water resistivity. By knowing the connection between water resistivity and corrosion rate, it is possible to monitor laboratory tests with water environments that have different levels of corrosiveness. Therefore, it is necessary to conduct an analysis to determine the effect of water resistivity on water corrosivity, understand the factors that influence the corrosion rate and calculate the corrosion rate of the irrigation gate steel plate on the water environment. This analysis uses a laboratory scale, analysis with talagasari irrigation water media, domestic wastewater, PDAM water and dead river estuary water. All water media used have a high level of corrosiveness. The factor that causes the low resistivity value is the large amount of inorganic minerals containing metal in the water so that at low resistivity values the corrosion rate increases. In the results of this laboratory analysis, it is proven that the more acidic the water medium, the faster the corrosion rate and the more alkaline the water medium, the slower the corrosion rate.